Antibacterial Activity Test of Star Fruit Leaf Extract (Averrhoa bilimbi Linn) Against Staphylococcus epidermidis - Elsen, Michellin; Rini, Desi Indria; Riwu, Magdarita; Wijaya, Carolin (Jurnal Biologi Tropis, 2026)
Staphylococcus epidermidis is a normal flora bacteria on the skin that can cause opportunistic infections. Generally, this infection is treated using antibiotics, but improper use of antibiotics can cause the onset of antibiotic resistance, so the development of natural antibacterial research with plant materials is one of the alternatives to reduce the incidence of resistance. A traditional medicinal plant is the leaves of star fruit (Averrhoa bilimbi Linn). This research aimed to investigate the antibacterial properties of the extract from star fruit leaves on Staphylococcus epidermidis. The type of research used is a true experimental design with a post-test only control group design. The treatment group in this study consisted of concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.12%, with a positive control of clindamycin at a dose of 2 μg and a negative control of sterile aquadest which was carried out 3 times for each test group. The antibacterial test method is carried out by the disc diffusion method. The data analysis used is the One Way Anova statistical test. Star fruit leaf extract contains alkaloid compounds, tannins, saponins, flavonoids, and steroids. There is antibacterial activity of star fruit leaf extract against Staphylococcus epidermidis. The inhibition zone was produced at various concentrations of 100% (⌀ 15.14 mm), 50% (⌀ 14.06 mm), 25% (⌀ 13.75 mm), 12.5% (⌀ 12.01 mm), 6.25% (⌀ 10.55 mm), and 3.12% (⌀ 9.03 mm). Starfruit leaf extract has antibacterial activity against Staphylococcus epidermidis.